2003
DOI: 10.1063/1.1618014
|View full text |Cite
|
Sign up to set email alerts
|

Bent silicon crystal in the Laue geometry to resolve x-ray fluorescence for x-ray absorption spectroscopy

Abstract: A highly strained, curved silicon crystal in the Laue geometry has been used as a large-area x-ray fluorescence analyzer for x-ray absorption spectroscopy. The analyzer is able to resolve the Lα fluorescence lines for neighboring actinide elements. A large gain in the signal to background ratio has been demonstrated for small quantities of Np in the presence of U, with the U fluorescence peak approaching 1000 times the magnitude of the off-peak background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…This is confirmed by recent x-ray absorption near-edge spectroscopy (XANES) studies that indicate the oxidation state of Np in the fuel matrix is Np(IV) and extended x-ray absorption fine structure (EXAFS) measurements that show the Np(IV) is present in a UO 2 -like phase. This is consistent with Np being in solid solution in the fuel's UO 2 fluorite lattice structure (Kropf et al 2005, Argonne 2005; see also this report, Section 3.4).…”
Section: Neptunium In Csnfsupporting
confidence: 79%
“…This is confirmed by recent x-ray absorption near-edge spectroscopy (XANES) studies that indicate the oxidation state of Np in the fuel matrix is Np(IV) and extended x-ray absorption fine structure (EXAFS) measurements that show the Np(IV) is present in a UO 2 -like phase. This is consistent with Np being in solid solution in the fuel's UO 2 fluorite lattice structure (Kropf et al 2005, Argonne 2005; see also this report, Section 3.4).…”
Section: Neptunium In Csnfsupporting
confidence: 79%
“…Bent crystal Laue analyzers (BCLAs) are alternative detection systems for these special and very limited cases. They cover absorption edges from Fe to Zn (Zhong et al, 1999;Kropf et al, 2003Kropf et al, , 2005. These analyzers offer a high background rejection and high energy resolution (up to $ 3.3 eV at 6.9 keV for our customdesigned BCLA for Ni, Cu and Zn spectral lines).…”
Section: Detectorsmentioning
confidence: 99%
“…Zhong's and Kropf's devices were limited to higher energies because the absorption of the fluorescence photons by the ∼140-200 microns thick crystal used. The need of thinner crystals for low energies down to 5 KeV was proposed by Kropf et al 8 but not reported before. Our device was designed for thin crystals to cover a lower energy range near Cu K lines.…”
Section: Analyzer Designmentioning
confidence: 92%
“…Previously, a BCLA device reported by Zhong et al 6 showed that this type of bending could be used for x-ray spectroscopy determinations for energies above 13 keV although their device lack soller slits that could reject the unwanted transmitted beam. Later, Kropf et al 8 developed a BCLA that incorporated soller slits, improving energy resolution, but not sufficient to resolve Kα 1 and Kα 2 lines in that energy range. Zhong's and Kropf's devices were limited to higher energies because the absorption of the fluorescence photons by the ∼140-200 microns thick crystal used.…”
Section: Analyzer Designmentioning
confidence: 99%
See 1 more Smart Citation